Quality of life correlation with socioeconomic status in Korean hepatitis-B patients: a cross sectional study - Kim, Seung Ju (Health Qual Life Outcomes, 2015)
BACKGROUND: In Korea, more than two-thirds of hepatocellular carcinoma patients are hepatitis B virus (HBV) surface antigen-seropositive. The effects of HBV infection on health-related quality of life (HRQoL) are important aspects in the overall management of HBV infection. However, other effects of other parameters on HBV patient HRQoL remain unknown and require clarification. Our study evaluated HRQoL in hepatitis-B patients, according to socioeconomic status. METHODS: We used community health survey data to analyze the relationship between HRQoL of HBV(+) patients according to socioeconomic status. We used propensity score matching (Ratio = 1:5) to balancing the patients and general population. Final analytic sample consisted of 7,098 hepatitis B patients and compared group (35,490 general populations). We examined the HRQoL in HBV(+) patients (n = 7,098), stratified by socioeconomic status, compared with general populations, using the EuroQOL visual analog scale (EQ-VAS) and EQ-5D questionnaires. We used the Chi-square test and ANOVA to compare demographic variables. Multiple linear regression analysis identified associations between demographic variables and HRQoL. RESULTS: Participants with hepatitis B numbered 7,098 (16.7 %) of the study population. HRQoL was lower in hepatitis-B patients compared to the general population (EQ-VAS: −0.985, p = 0.0004; EQ-5D: −0.673, p = 0.0003). According to occupation type, clerks (EQ-VAS: −2.628, p = 0.0030; EQ-5D: −0.802, p = 0.0099) and managers and professionals (EQ-VAS: −1.518, p = 0.0356) had the lowest HRQoLs. Higher family income and education level groups had lower HRQoLs compared to the general population. CONCLUSIONS: Patients from higher socioeconomic status groups had HRQoLs that were more affected by hepatitis B. Thus, we require more accurate information about the disease to develop appropriate patient management guidelines. This will facilitate formulating policies and management strategies that alleviate HRQoL declines in HBV(+) patients.